Identification of metabolites in plasma for predicting survival in glioblastoma. Issue 8 (16th April 2018) - Shen, Jie; Song, Renduo; Hodges, Tiffany R.; Heimberger, Amy B.; Zhao, Hua
Abstract : Circulating metabolomics profiling holds prognostic potential. However, such efforts have not been extensively carried out in glioblastoma. In this study, two‐step (training and testing) metabolomics profiling was conducted from the plasma samples of 159 glioblastoma patients. Metabolomics profiling was tested for correlation with 2‐year overall and disease‐free survivals. Arginine, methionine, and kynurenate levels were significantly associated with 2‐year overall survival in both the training and testing sets. In the combined sets, elevated levels of arginine and methionine were associated with a 34% and 37% increased probability whereas kynurenate was associated with a 55% decreased probability of 2‐year overall survival. These three metabolites were also significantly associated with 2‐year disease‐free survival. Risk scores were generated using the linear combination of levels of these significant metabolites. Glioblastoma patients with a high‐risk score exhibited a 2.41‐fold decreased probability of 2‐year overall survival (hazard ratio (HR) = 2.41; 95% Confidence Interval (CI) = 1.20‐4.93) and a 3.17‐fold decreased probability of 2‐year disease free survival (HR = 3.17, 95%CI = 1.42‐7.54) relative to those with a low‐risk score. In conclusion, we identified a unique plasma metabolite profile that is predictive of glioblastoma prognosis.